Investigation of Potential Inhibitors of Chorismate-Utilizing Enzymes - Svarcova, Marketa; Kratky, Martin; Vinsova, Jarmila (Current Medicinal Chemistry, 2015)
Chorismate-utilizing enzymes (CUE) such as chorismate mutase, anthranilate synthase, chorismate pyruvate-lyase, 4-amino-4-deoxychorismate synthase, isochorismate synthase and salicylate synthase are responsible for converting chorismate into various products necessary for the survival of bacteria. The absence of these enzymes in humans and their importance in the virulence and survival of bacteria make them suitable targets for potential antimicrobial compounds. Furthermore, the CUE have significant structural homology and similar catalytic mechanisms, enabling the strategy of affecting multiple enzymes with one single inhibitor. This review follows up the investigation of mechanisms of CUE-catalysed reactions and the concurrent development of CUE inhibitors. Many active compounds were found amongst the structures mimicking the transition state of chorismate during the reaction. Most recently, high nanomolar and low micromolar inhibitors against isochorismate-pyruvate lyase were identified, which were also effective against chorismate mutase and salicylate synthase and belong to the most active inhibitors reported up to date.
Keywords: chorismate utilizing enzymes